Adjuvant Therapeutic Modalities in Primary Small Cell Carcinoma of Esophagus Patients: A Retrospective Cohort Study of Multicenter Clinical Outcomes. Issue 17 (April 2016) - Zou, Bingwen; Li, Tao; Zhou, Qiang; Ma, Daiyuan; Chen, Yongshun; Huang, Meijuan; Peng, Feng; Xu, Yong; Zhu, Jiang; Ding, Zhenyu; Zhou, Lin; Wang, Jin; et al.
Abstract : Abstract: To evaluate the treatment pattern and survival of patients receiving radical resection for primary small cell carcinoma of the esophagus (PSCCE). This retrospective study included 150 patients who received radical resection of PSCCE. Data were retrieved from 4 centers in Western China. Thirty-nine of 150 patients received postoperative chemo-radiotherapy, 62 received postoperative chemotherapy, and 49 received radical resection only. The median radiation dosage was 50 Gy. The chemotherapeutic regimen was platinum-based and lasted for 2 to 6 cycles (median, 3). Median disease-free survival (mDFS) and overall survival (mOS) were 12.0 and 18.3 months, respectively. Subgroup analysis revealed that postoperative therapy did not improve survival in limited stage I (LSI) disease, whereas postoperative chemotherapy improved survival in limited stage II (LSII) disease. Relative to chemotherapy alone, chemoradiotherapy did not improve survival in patients with completely resected LSII disease. A multivariate analysis indicated an association of no postoperative chemotherapy with shorter DFS ( P = 0.050) and OS ( P = 0.010). Higher lymph node stage and length of disease longer than 3 cm were poor prognostic factors for both DFS and OS. Adjuvant chemotherapy improves survival in PSCCE patients with completely resected LSII disease. Adjuvant treatment with postoperative chemotherapy alone or postoperative chemo-radiotherapy does not increase survival in completely resected LSI disease.